Analysis of Suitable Habitat for Nesting of Hawksbill Turtles (Eretmochelys imbricata) in Pulau Sangiang Natural Park, Banten - Jannah, Neisya Rachmah Raudhatul; Cahyadi, Ferry Dwi; Sasongko, Agung Setyo; Handayani, Dwi (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2024)
The Sangiang Island Nature Tourism Park (TWA Pulau Sangiang) is a small island in the Sunda Strait that serves as a nesting habitat for hawksbill turtles (Eretmochelys imbricata). This study aims to analyze the suitability of beaches in TWA Pulau Sangiang as a nesting site. The research employs a qualitative method with direct field observation techniques, interviews, and documentation. The data measured include beach slope, beach width, nest temperature, nest humidity, beach sand pH, sand substrate, beach vegetation, natural predators, and human disturbances. The data were analyzed descriptively using a habitat suitability index for turtle nesting. The measurements show that Villa Bubu Beach has a beach width of 6.4 meters with an average slope of 10º. The sand substrate on this beach is dominated by 97.38% medium sand. Nest temperatures on this beach are 28℃ with dry humidity and an average pH ranging from 6.5 to 7. Meanwhile, Sepanjang Beach has an average beach width of 27.15 meters with a slope ranging from 9.1º. The sand substrate is dominated by 99.47% medium sand. Nest temperatures on this beach average 30℃ with dry humidity and a pH of 6.5–7. The coastal vegetation at Villa Bubu Beach is dominated by Casuarina trees (Casuarina equsetifolia), while the vegetation at Sepanjang Beach is dominated by Sea Lettuce Trees (Scaevola taccada) and Screw Pines (Pandanus tectorius). Natural predators on both beaches include monitor lizards and wild boars. Based on these measurements, Villa Bubu Beach and Sepanjang Beach in TWA Pulau Sangiang are highly suitable as nesting habitats for hawksbill turtles.